Recent Progress in the Design of Monodisperse, Sequence‐Defined Macromolecules. Issue 9 (15th March 2017) - Solleder, Susanne C.; Schneider, Rebekka V.; Wetzel, Katharina S.; Boukis, Andreas C.; Meier, Michael A. R.
Abstract : A review of synthesis procedures leading to monodisperse and sequence‐defined linear macromolecules, including conjugated and non‐conjugated oligomers, is presented. The approaches are summarized and analyzed in terms of applicability in polymer science. Simple synthesis procedures, scales, overall yields, achievable level of control, and the purity of the obtained macromolecules are important benchmarks. Abstract : This review describes different synthetic strategies towards sequence‐defined, monodisperse macromolecules, which are built up by iterative approaches and lead to linear non‐natural polymer structures. The review is divided in three parts: solution phase‐, solid phase‐, and fluorous‐ and polymer‐tethered approaches. Moreover, synthesis procedures leading to conjugated and non‐conjugated macromolecules are considered and discussed in the respective sections. A major focus in the evaluation is the applicability of the different approaches in polymer chemistry. In this context, simple procedures for monomer and oligomer synthesis, overall yields, scalability, purity of the oligomers, and the achievable level of control (side‐chains, backbone, stereochemistry) are important benchmarks.